NLP MODELLING TECHNIQUE IN REDUCING PRONUNCIATION ERRORS - Yousef Bani Ahmad; Abduloh Abduloh (English Language Teaching and Research, 2018)
This study aims to determine modelling techniques in Neuro Linguistic Programming (NLP) in reducing the pronunciation errors of students. In this study, researcher used a qualitative approach with descriptive methods. Subjects in this study were English education students who took the English Spelling Corner (ESC) program. This research data was obtained from observation, interviews and documentation. There were 6 samples taken from students who participated in the spelling corner program. The results of this study designated that in learning English pronunciation by using NLP modelling techniques, students are able to practice according to the right way. This technique is able to make students easier to pronounce English by modelling native speakers in the video material that has been prepared in learning activity. Wherefore, it is easy to model English pronunciation directly from native speakers, students are able to reduce errors in aspects of the pronunciation such as vowel sounds, consonant sounds, stress in English syllables, intonation and even accents like native speakers. The impact on English learners is that the quality of the English pronunciation of students who take the English spelling corner is getting better and more self-assured.Key words: Pronunciation, Neuro Linguistic Programming, Vowel and Consonant Sounds